Information and communication technology development indices (UN New YorkUS, 2003)
Analyses and evaluated information and communication technology (ICT) development using indicators of ICT difusion across countries. Develops a conceptual framework for measuring ICT development. Selects key indicators for doing likewise, with a specific focus on information and communication technologies (ICTs) as pervasive technologies of global impact, wide application and growing potential.
Keywords: INFORMATION TECHNOLOGY